2011
DOI: 10.3109/10641963.2010.503299
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Angiotensin II Receptor Antagonist with Calcium Channel Blocker or Diuretic as Antihypertensive Therapy for Patients with Chronic Kidney Disease

Abstract: We compared treatment with an angiotensin II receptor antagonist (ARB) and a calcium channel blocker (CCB) combination and a fixed-dose ARB and thiazide diuretic in 18 chronic kidney disease (CKD) patients. A randomized crossover study was performed using a fixed-dose combination of losartan-hydrochlorothiazide or losartan combined with controlled-release nifedipine. Both systolic blood pressure (SBP) and diastolic blood pressures (DBPs) were lower during the nifedipine period than during the diuretic period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…1 ). One study was based on a cross-over RCT, [ 24 ] and 13 studies were based on parallel RCTs. The final 14 RCTs consisted of a total of 18,125 patients with hypertension.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). One study was based on a cross-over RCT, [ 24 ] and 13 studies were based on parallel RCTs. The final 14 RCTs consisted of a total of 18,125 patients with hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…The final 14 RCTs consisted of a total of 18,125 patients with hypertension. Among them, 8 RCTs recruited Asian subjects only, [ 13 15 , 18 , 20 , 21 , 23 , 24 ] while the other 6 RCTs were conducted in either mixed-race or unmentioned-race populations. Six RCTs compared the 2 combined treatments in 1001 patients with diabetes mellitus, [ 13 , 14 , 16 , 17 , 22 , 25 ] and 3 RCTs compared treatments in 1079 CKD patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the change of eGFR level, the required sample size for detecting a five difference with SD=16 between the two treatment arms (type I error, one sided α=0.025, power 1−β=0.90) was about 217 for each arm (434 in total) according to Ishimitsu et al 's study 6. The formula isu α =1.96, u β =1.282, δ=5, σ=16.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Hayashi et al 5 found the addition of diuretics or CCB to ARB was equally effective for the control of HTN in CKD, while diuretics may be better than CCB in reducing proteinuria (PROTECT study). However, Ishimitsu et al 6 found losartan plus nifedipine showed a superior antihypertensive and renoprotective effect in CKD patients compared to losartan plus HCTZ, but nifedipine was not associated with lower urinary albumin excretion compared to HCTZ. The ACCOMPLISH study7 concluded that hypertensive patients treated with benazepril plus amlodipine had a lower risk of progression to CKD than those treated with benazepril plus HCTZ.…”
Section: Introductionmentioning
confidence: 98%